2020
DOI: 10.3390/bs10040078
|View full text |Cite
|
Sign up to set email alerts
|

Smoking Status and Well-Being of Underserved African American Older Adults

Abstract: Purpose: This study investigated the association between current and past cigarette smoking, with four domains of well-being, namely, physical quality of life, mental quality of life, depressive symptoms, and self-rated health status (SRH), among older African American adults who lived in economically impoverished areas of South Los Angles. Methods: This community-based cross-sectional study included a convenience sample of economically-disadvantaged African Americans adults (n = 740) who were 55 years old and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 73 publications
2
4
0
Order By: Relevance
“…Age was inversely associated with tobacco use among older adults. Consistent with previous studies, current smokers were younger than never-smokers and past smokers among African American older adults in South Los Angeles in the U.S. [36] and older men, in particular in Korea [78] and Iran [79]. This might be because older adults felt more vulnerable due to increasing health problems with age.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Age was inversely associated with tobacco use among older adults. Consistent with previous studies, current smokers were younger than never-smokers and past smokers among African American older adults in South Los Angeles in the U.S. [36] and older men, in particular in Korea [78] and Iran [79]. This might be because older adults felt more vulnerable due to increasing health problems with age.…”
Section: Discussionsupporting
confidence: 88%
“…", was used to collect information regarding smoking from the respondents. Respondents who answered "never" to the question were classified as never-smokers, participants who answered "ever" to the question were classified as past smokers, and those who answered "occasionally or regularly" to the question were classified as current smokers [2,36]. In the current research, never-smokers and past smokers were combined and constituted the non-smoker category [35], and occasional or regular smokers were categorized as current smokers [16].…”
Section: Tobacco Usementioning
confidence: 91%
See 2 more Smart Citations
“…A recent systematic review also reported a positive association between cigarette smoking and depressive symptoms among non‐pregnant adults (Fluharty, Taylor, Grabski, & Munafò, 2017). In a study with Black adults ages 55 or older who lived in economically impoverished urban areas, participants who smoked cigarettes reported more depressive symptoms compared with participants who did not smoke cigarettes (Bazargan, Cobb, Castro Sandoval, & Assari, 2020). In another study with a sample with women who smoked (83 European American and 175 African American), smoking was significantly correlated with depressive symptoms among African American women only (Ludman et al, 2002).…”
Section: Introductionmentioning
confidence: 99%